Application of Personnel Management Information System (SIMPEG) in the Process of Mutation / Transfer of State Civil Apparatus at BKPSDMD Makassar City - Akib, Haedar; Arifin, Muhammad; Ismail, Ismail; Aina, Asri Nur (Universitas Negeri Makassar, 2024)
This study aims to determine the Application of the Personnel Management Information System (SIMPEG) in the process of mutation / transfer of state civil apparatus in BKPSDMD Makassar City. This research includes descriptive Qualitative Research with data collection techniques through observation, interviews, and documentation. Data analysis techniques consist of data reduction, data translation and conclusions.The results showed that the application of the Personnel Management Information System (SIMPEG) in the mutation / transfer of the state civil apparatus in the BKPSDMD Makassar City. With the presence of the Personnel Management Information System (SIMPEG) at the Regional Human Resources and Management Personnel Agency (BKPSDMD) Makassar City provides good benefits to all BKPSDMD employees who use SIMPEG. By changing the Manual Pattern to an all-Digital one. This will help reduce the risk of errors and speed up the overall ASN mutation process. When viewed from several dimensions of Rivai Personnel Information System Criteria (2009), namely Timely, Accurate, Relevant, and Complete. However, it needs to be optimized on the Just-in-Time Dimension because with the problem of the network / server can inhibit the ASN mutation process. For this reason, BKPSDMD prioritizes having a reliable network infrastructure so that the Mutation / Transfer of State Civil Apparatus in BKPSDMD Makassar City runs smoothly.